Revolutionizing General Trias building a future-ready city through the ICT (Information and Communications Technology) Literacy and Competency Development Training Center through scenario building - Custodio, Christopher N. (University of the Philippines Diliman, 2023)
The City of General Trias acknowledges the importance of information and communication technology (ICT) in molding the city's future and plans to construct an ICT Literacy and Competency Development Training Center. This study provides an outlook of the planned training center, its goals, and the possible advantages it would deliver to the city's citizens, companies, and economy in the future.